History of Pototan, Iloilo. - Parcon, Genalyn Porras
This is a study of the history of Pototan from pre-Spanish period up to the present that focuses on the socio-cultural, political, educational, and economic development of the town. This study aims to discover the following: 1) to know where the name "Pototan" originated and when was it established as a town; 2) to identify who were the early settlers of the town and where they came from; 3) to specify what the socio-cultural, political and economic conditions of Pototan were during the pre-Spanish period; 4) to describe the development and various effects of Spanish, American and Japanese occupation in the town; 5) to discuss the developments that transpired in Pototan after World War II and its contribution to the province of Iloilo., Sources used were categorized into primary and secondary. Primary sources were based on interview with the town's folk who were knowledgeable about the town. Interviews were conducted in vernacular and in either formal or informal set-up with guide questions. Secondary data were taken from books, government documents, souvenir programs and other related materials such as old maps and manuscripts. The validity of the gathered data from interviews was cross-examined through published books. The first settlers of Pototan were the family of Datu Lumangoy and his followers who came from Dumangas. They had no surnames, so when the Augustinians arrived in Panay they baptized the natives and Datu Lumangoy was given a Christian name "Jose Patriarca". The name Pototan originated from the word "kaputan" which means a place where putat trees grow abudantly. Pototan, before, was a mere sitio of the town Dumangas, but, in 1749, the Spaniards organized it into a pueblo separate from its matrix Dumangas. Upon the arrival of the different colonizers, the life of Pototanons rapidly changed. The Spaniards colonized the Filipinos for more than 300years, the Americans for almost 40 years and the Japanese for 3 years. These years of occupation of different colonial masters led to a mixture of a Filipino identity. During the Spanish era, the economic development in Pototan was greatly affected because of economic policies imposed by the Spaniards. Moreover, when the Americans occupied Pototan, the political sector of the town was enhanced. Women were given the right to vote and the natives also enjoyed the freedom of speech, worship and education. On the other hand, the Japanese occupation of the town spread chaos and fear among the Pototans. Agricultural facilities were destroyed as well as infrastructures. The people suffered so much because of food shortage and Japanese brutalities. However, after the war, the Pototanons worked hand in hand in restoring what was left on them. The people returned to their farms and cultivated rice, sugarcane, tobacco, corn, peanuts and different fruits and vegetables. Others continued to enagage in various forms of cottage industry such as basket, sawali, cararaw, amakan, and bolo binangon (bolo) making; and poultry and livestock raising in which some had financial assistance fromt the government.